(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Teachers are the ones who can pull out individuals from the darkness of lack of expertise intothe light of knowledge. Education, the most important factor for us, can’t provide a nation with doctors,engineers, scientists, officers etc. Teachers make their students academically robust and they constantlyencourage their students to do higher in their life. In the words of Saint Kabir, “the value of a trainer isextra in comparison to god and we should be grateful to our teachers” A Teacher is additionally referredto as as “Guru” and in ancients times, human beings used to tackle a trainer via ,’Guru’ human beingsused to leave in Gurukuls to attend academic knowledge.